2022
DOI: 10.3389/fmed.2021.817305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and BMI on the VWF/ADAMTS13 Axis and Simultaneous Thrombin and Plasmin Generation in Hospitalized COVID-19 Patients

Abstract: Aging and obesity independently contribute toward an endothelial dysfunction that results in an imbalanced VWF to ADAMTS13 ratio. In addition, plasma thrombin and plasmin generation are elevated and reduced, respectively, with increasing age and also with increasing body mass index (BMI). The severity risk of Corona Virus Disease 2019 (COVID-19) increases in adults older than 65 and in individuals with certain pre-existing health conditions, including obesity (>30 kg/m2). The present cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
(107 reference statements)
2
8
1
Order By: Relevance
“…In this study we observed a significant increase in TG parameters induced by addition of COVID-19 (+) patient plasma isolated LEVs compared to COVID-19 (+) patient SEVs and compared to healthy donor plasma isolated SEVs and LEVs. TG associated with the COVID-19 (+) patients LEV fraction of plasma accumulated EVs in this study supports an observation of increased TG in COVID-19 (+) patient versus acutely ill patient plasmas upon hospital presentation and admission 62 . This study does have several limitations as follows: all samples from confirmed COVID-19 (+) patients were obtained within 1-3 days of hospital admission which may alter the cargo of both SEVs and LEVs and temporal samples over the course of hospital stay to assess progressive disease were not obtained.…”
Section: Discussionsupporting
confidence: 86%
“…In this study we observed a significant increase in TG parameters induced by addition of COVID-19 (+) patient plasma isolated LEVs compared to COVID-19 (+) patient SEVs and compared to healthy donor plasma isolated SEVs and LEVs. TG associated with the COVID-19 (+) patients LEV fraction of plasma accumulated EVs in this study supports an observation of increased TG in COVID-19 (+) patient versus acutely ill patient plasmas upon hospital presentation and admission 62 . This study does have several limitations as follows: all samples from confirmed COVID-19 (+) patients were obtained within 1-3 days of hospital admission which may alter the cargo of both SEVs and LEVs and temporal samples over the course of hospital stay to assess progressive disease were not obtained.…”
Section: Discussionsupporting
confidence: 86%
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the time of sample collection varied and could attribute to different outcome measures. Fourth, due to the lack of individual patient data, multivariable regression analyses could not be performed to adjust for potential confounding influences (e.g., blood type, age, sex, body mass index, diabetes, hypertension, and medication usage) [82] , [170] . Despite these limitations, this study represents a large systematic reviews and meta-analysis to investigate the association between changes in VWF-related variables and clinical outcomes in the COVID-19 population.…”
Section: Discussionmentioning
confidence: 99%
“…302 Additional studies related to this, or the topic of the ADAMTS13/VWF “axis” or relative imbalance in various disease processes, are also evident in the reference list (e.g., references). 92 143 147 152 153 169 184 226 245 262 272 300 302 305 306…”
Section: Discussionmentioning
confidence: 99%